MULTIMEDIA INTERAKTIF COMPANY PROFIL UNIVERSITAS STIKUBANK SEMARANG “ FAKULTAS TEKNOLOGI INFORMASI” SEBAGAI MEDIA PROMOSI INTERACTIVE MULTIMEDIA COMPANY PROFILE OF UNIVERSITY STIKUBANK SEMARANG "FACULTY OF TECHNOLOGY INFORMATION" AS MEDIA PROMOTION (Information Technology and Telematics, 2015)
Abstract Media promotion is a very important tool as a means to communicate a product, service, or company or the other to be better known by the wider public, the media campaign in the delivery of a complete and detailed information about the University of Semarang Stikubank ranging from history, the quality of quality, facilities until the excess found in Stikubank University of Semarang. With the realization Company Profile Stikubank University of Semarang, the expected public and target audience can get to know about the existence Stikubank University of Semarang. The purpose of this research is to design and create an Interactive Multimedia applications company profile Stikubank Semarang University "Faculty of Information Technology" as a media campaign. This study uses the methodology Multimedia Development. which consists of 6 stages, namely the concept, design, collecting materials, assembly, testing and distribution. The results of this study in the form of CD Company Profile Stikubank Semarang University "Faculty of Information Technology". This application is made interactively so that users do not only see, but also to respond by selecting the desired material contained in the main menu Keywords:, company profiles, interactive multimedia, CD